Can the TLR-4-Mediated Signaling Pathway Be "A Key Inflammatory Promoter for Sporadic TAA"?. (9th July 2014) - Ruvolo, Giovanni; Pisano, Calogera; Candore, Giuseppina; Lio, Domenico; Palmeri, Cesira; Maresi, Emiliano; Balistreri, Carmela R.
Abstract : Thoracic aorta shows with advancing age various changes and a progressive deterioration in structure and function. As a result, vascular remodeling (VR) and medial degeneration (MD) occur as pathological entities responsible principally for the sporadic TAA onset. Little is known about their genetic, molecular, and cellular mechanisms. Recent evidence is proposing the strong role of a chronic immune/inflammatory process in their evocation and progression. Thus, we evaluated the potential role of Toll like receptor- (TLR-) 4-mediated signaling pathway and its polymorphisms in sporadic TAA. Genetic, immunohistochemical, and biochemical analyses were assessed. Interestingly, the rs4986790 TLR4 polymorphism confers a higher susceptibility for sporadic TAA (OR = 14.4, P = 0.0008 ) and it represents, together with rs1799752 ACE, rs3918242 MMP-9, and rs2285053 MMP-2 SNPs, an independent sporadic TAA risk factor. In consistency with these data, a significant association was observed between their combined risk genotype and sporadic TAA. Cases bearing this risk genotype showed higher systemic inflammatory mediator levels, significant inflammatory/immune infiltrate, a typical MD phenotype, lower telomere length, and positive correlations with histopatological abnormalities, hypertension, smoking, and ageing. Thus, TLR4 pathway should seem to have a key role in sporadic TAA. It might represent a potential useful tool for preventing and monitoring sporadic TAA and developing personalized treatments.